CMZoom III: Spectral line data release. Issue 3 (6th February 2023) - Callanan, Daniel; Longmore, Steven N; Battersby, Cara; Hatchfield, H Perry; Walker, Daniel L; Henshaw, Jonathan; Keto, Eric; Barnes, Ashley; Ginsburg, Adam; Kauffmann, Jens; Kruijssen, J M Diederik; Lu, Xing; et al.
ABSTRACT: We present an overview and data release of the spectral line component of the SMA Large Program, CMZoom. CMZoom observed 12 CO (2–1), 13 CO (2–1), and C 18 O (2–1), three transitions of H2 CO, several transitions of CH3 OH, two transitions of OCS, and single transitions of SiO and SO within gas above a column density of N(H2 ) ≥ 10 23 cm −2 in the Central Molecular Zone (CMZ; inner few hundred pc of the Galaxy). We extract spectra from all compact 1.3 mm CMZoom continuum sources and fit line profiles to the spectra. We use the fit results from the H2 CO 3(0, 3)–2(0, 2) transition to determine the source kinematic properties. We find ∼90 per cent of the total mass of CMZoom sources have reliable kinematics. Only four compact continuum sources are formally self-gravitating. The remainder are consistent with being in hydrostatic equilibrium assuming that they are confined by the high external pressure in the CMZ. We find only two convincing proto-stellar outflows, ruling out a previously undetected population of very massive, actively accreting YSOs with strong outflows. Finally, despite having sufficient sensitivity and resolution to detect high-velocity compact clouds (HVCCs), which have been claimed as evidence for intermediate mass black holes interacting with molecular gas clouds, we find no such objects across the large survey area.